We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
196
1
avatar+380 

If \(\displaystyle{f(x)=x^{(x+1)}(x+2)^{(x+3)}}\), then find the value of \(f(0)+f(-1)+f(-2)+f(-3)\).

 Feb 17, 2019
 #1
avatar+557 
+3

f(x)=x^(x+1)*(x+2)^(x+3)

f(0)=0^(0+1)*(0+2)^(0+3)

f(0)=0^1*2^3

f(0)=0*8

f(0)=0

f(-1)=1

f(-2)=0

f(-3)=1/9

f(0)+f(-1)+f(-2)+f(-3)=10/9

0+1+0+(1/9)=10/9

 

 

winkwinkwink

 Feb 17, 2019

17 Online Users